2019
DOI: 10.1038/s41467-019-08724-x
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced inactivation of the Staphylococcus aureus purine biosynthesis repressor leads to hypervirulence

Abstract: Staphylococcus aureus is a significant cause of human infection. Here, we demonstrate that mutations in the transcriptional repressor of purine biosynthesis, purR, enhance the pathogenic potential of S. aureus. Indeed, systemic infection with purR mutants causes accelerated mortality in mice, which is due to aberrant up-regulation of fibronectin binding proteins (FnBPs). Remarkably, purR mutations can arise upon exposure of S. aureus to stress, such as an intact immune system. In humans, naturally occurring an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 54 publications
(45 reference statements)
14
58
0
Order By: Relevance
“…To do this, we infected mice IV with each of the four strains using a well-established model of murine bacteraemia. While WT infected animals steadily lost weight over the course of the 4 days of infection, animals infected with the purR mutant required sacrifice at 24 hpi, as previously demonstrated (10) (Fig 1A), and this correlated with significant increases in bacterial burden, versus WT, in the heart and kidneys at 24 hpi ( Fig 1B). In contrast, animals infected with the purK mutant did not lose weight ( Fig 1A), or show outward signs of disease, even by 96 hpi, and had significantly lower bacterial burden in the heart and kidneys ( Fig 1C).…”
Section: De Novo Purine Biosynthesis Is Required For S Aureus Replicsupporting
confidence: 76%
See 2 more Smart Citations
“…To do this, we infected mice IV with each of the four strains using a well-established model of murine bacteraemia. While WT infected animals steadily lost weight over the course of the 4 days of infection, animals infected with the purR mutant required sacrifice at 24 hpi, as previously demonstrated (10) (Fig 1A), and this correlated with significant increases in bacterial burden, versus WT, in the heart and kidneys at 24 hpi ( Fig 1B). In contrast, animals infected with the purK mutant did not lose weight ( Fig 1A), or show outward signs of disease, even by 96 hpi, and had significantly lower bacterial burden in the heart and kidneys ( Fig 1C).…”
Section: De Novo Purine Biosynthesis Is Required For S Aureus Replicsupporting
confidence: 76%
“…Previously, we showed that FnBPs are essential for the hypervirulence of a purR mutant (10). However, it was not known whether FnBP expression is sufficient for this phenotype, or whether the concurrent increase in pur gene expression contributes to rapid lethality in mice.…”
Section: De Novo Purine Biosynthesis Is Required For S Aureus Replicmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the virulence genes chp, coa, ssl11, sbi, map, lukA, and scn , previously reported to be under the control of SaeRS 44 , were also found in this i-modulon. PurR, a transcription factor that regulates the genes of purine biosynthesis, has been recently implicated in regulation of virulence factors 45,46 . Consistent with this observation, the activity level of the SaeR i-modulon correlated well (PearsonR = 0.77, p-value = 8.9e-23) with the activity of the PurR i-modulon ( Figure 5b ).…”
Section: Ica Reveals Organization Of Virulence Factor Expressionmentioning
confidence: 99%
“…In our study, the cap genes were all belong to cap5 or cap8 gene clusters. Fibronectin-binding protein A (FnbA) and FnbB are known as important adhesions for S. aureus and contribute to mediate cellular invasion, and promote virulence during infection (45, 46). Indeed, previous work has demonstrated that the global regulators of staphylococcal virulence Agr and Sar coordinate FnbA expression (47).…”
Section: Discussionmentioning
confidence: 99%